THE STRANGE IN LEO N. TOLSTOY’S ARTISTIC WORLD (CASE STUDY OF THE SHORT STORY “WHY”?) - Yunusov, Ildar; Abdullina, Amina; Karamova, Aigul; Khasanov, Rishat; Yunusova, Faniya (Revista Inclusiones, 2020)
It has been known for a long time that Leo Tolstoy could comprehend the strange worlds – a person of other social standing, a person of a different sex (a woman during her childbirth), animals, people of different ethnic groups, religions, civilizations. But his ability to comprehend a person of a different culture, of a strange ethnic group that is even hostile for your people, assumed quite a new dimension in the last decades. This ability of Leo Tolstoy is scarce and in great demand in the modern world. From the end of the 1980-s to the present day, such research practices as mythopoetics (in the context of the binary opposition “ friendly – strange”), imagology, the post-colonial theories, which are used in this article to one degree or another, were on the foreground of the literary science. That’s why this paper is important today. This research is aimed at detecting peculiarities of comprehending the strange in Leo Tolstoy’s artistic world, namely in his short story “Why?”.